Integrated rural socio-economic vulnerability analysis in Lampung Province - Dedy Yuliawan; Dedi Budiman Hakim; Bambang Juanda; Akhmad Fauzi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
One of the common characteristics of rural areas is their vulnerability to socio-economic and environmental shocks. Therefore, rural development policies should consider these features to take full advantage of the benefits of rural development. This study aims to develop a pastoral assessment based on the TOPSIS-Etropy-Inhomogeneity Method. This research was conducted in Lampung Province using data at the regency level. The data uses village data from the 2018 Village Potential Survey (PODES). The results show that rural areas' exposure, sensitivity, and adaptive capacity factors play an essential role in rural development regarding vulnerability and resilience. Pesisir Barat, Mesuji, and Tulang Bawang Regencies are highly susceptible to low adaptation factors such as difficult access to health centers, inadequate credit facilities from the government, quiet village anticipation and mitigation, and a lack of security systems. The lowest vulnerabilities are in Tanggamus and North Lampung Regencies with common sensitivity factors, where people with malnutrition, persons with disabilities, households living in slums, and the habit of not using river water or the like for drinking or cooking have lower scores. In addition, other factors contribute to vulnerability, and these factors should be considered in rural development policies